Building communities and simulating the nation Politics of engaging the "other" in the first season of survivor Philippines. [article]. - Contreras, Antonio P.
Modernist and integrationist theories tend to see the process of nation building as a "game" of surviving. However, the idea of a "surviving" nation, which is shaped according to the logic of the game of politics as domination, is antithetical to the organic processes of institution building consistent with habitus of the diverse social formations which are found in the Philippines. In these organic spaces, a unified community is born not out of an idea of subordinated "other" being eliminated, but of "others" being accommodated in the larger society. Survival is not an invidualistic and Darwinian process of weeding out the weak, but as a communitarian invitation towards a shared meaning system that is drawn from positions of difference, in which the other is not subordinated, but is just different, and in which the idea of sovereignty is not colonizing the sense of autonomy of these different subjectivities. This theoretical argument will be supported by how the Philippine adaptation of the Survivor franchise, through the first season of the reality TV program Survivor Philippines, has effectively confronted the western construct inherent in the very idea of the game, as seen on how it is played in its American versions. How the game was played, crafted and interpreted in its Filipino version has challenged the Machiavellian concept of politics, and theDarwinian idea of survival of the fittest. This is done by depicting the process of building communities from the fragments of multiple identifies as one in which the politics of conflict and contestation is resolved not towards elimination and assimilation of the defeated weaker "other", but of accommodation and tolerance of those who are just different. -- (from the author)